Trend Penerbitan Kajian Hak Kebebasan Beragama di Malaysia: Sebuah Kajian Bibliomatrik - Ain Balkis Mohd Azam; Kamal Azmi Abd Rahman; Khadijah Muda; Abd Hakim Mohad @ Mohamad Ramli; Adibah Sulaiman; Sarjit Singh Darshan Singh (Universiti Sains Islam Malaysia, 2024)
Sains Insani, Volume 9 Issue 1 Page (7-13)